RETRACTED- SEASONAL AFFECTIVE DISORDER AMONG UNDERGRADUATE STUDENTS IN PESHAWAR DISTRICT: A retraction has been issued for this article: (DOI: https://doi.org/10.63050/jpps.22.1.1047) - Jamal, Izaz; Khalil, Aimen; Faiz, Tabassum; Gul, Ejaz; Mufti , Ali Ahsan; Pirzada, Muhammad Muneeb (Journal of Pakistan Psychiatric Society, 2024)
OBJECTIVETo find the frequency of seasonal changes on undergraduate students and make a comparison between undergraduate students on the basis of the prevalence of Seasonal affective disorder. (SAD).STUDY DESIGNCross-sectional studyPLACE & DURATION OF STUDYData were collected from different universities in Peshawar city, including Khyber Medical University, Abasyn University, Peshawar University, Cecos University, and Rehman Medical Institute, from 7 January 2022 to 17 November 2022.METHODThe sample size consisted of 100 undergraduate students from different universities in Peshawar (N = 100). Their ages ranged from 18 to 26 years old. The Seasonal Pattern Assessment Questionnaire (SPAQ) along with a demographic information sheet and informed consent sheet were administered.RESULTSResults revealed that among 100 participants, 71 were affected by SAD. Further on, it was elaborated that female students have high rates of SAD as compared with male students.CONCLUSIONThe results of the study confirmed the presence of seasonal affective disorder among undergraduate students with a large female population being affected by it.